2015
DOI: 10.5339/gcsp.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for hypertension: A cross-sectional study in an urban area of Bangladesh

Abstract: Background: Hypertension is a major risk factor for several cardiovascular diseases (CVD). The prevalence of hypertension is increasing in Bangladesh, especially in urban areas. The objective of this study was to estimate the prevalence of hypertension and its risk factors in an urban area of Bangladesh. Methods: We conducted a cross-sectional survey involving participants aged ≥ 25 years in an urban area in Dhaka between June-December 2012, using multi-stage random sampling. Data on socioeconomic status, toba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
5
39
1
Order By: Relevance
“…100 Extra salt intake along with age, BMI, physical inactivity, tobacco use and family history of stroke/CVD was found to have significant relationship with hypertension and pre-hypertension in a cross-sectional survey involving participants aged e" 25 years in an urban area in Dhaka between June to December 2012. 101 Also, more than 35 million people in coastal Bangladesh are vulnerable to increasing freshwater salinization; elevated salinity in drinking water has been found to be associated with higher BP in young coastal populations. 102 The overall risk perception regarding excessive salt consumption is low and there is widespread belief that the cooking process can render the salt harmless.…”
Section: Lifestyle Related Factorsmentioning
confidence: 99%
“…100 Extra salt intake along with age, BMI, physical inactivity, tobacco use and family history of stroke/CVD was found to have significant relationship with hypertension and pre-hypertension in a cross-sectional survey involving participants aged e" 25 years in an urban area in Dhaka between June to December 2012. 101 Also, more than 35 million people in coastal Bangladesh are vulnerable to increasing freshwater salinization; elevated salinity in drinking water has been found to be associated with higher BP in young coastal populations. 102 The overall risk perception regarding excessive salt consumption is low and there is widespread belief that the cooking process can render the salt harmless.…”
Section: Lifestyle Related Factorsmentioning
confidence: 99%
“…These findings are similar to other studies among adults in Bangladesh and India. 33,39 There were certain limitations in this study. First of all, cross-sectional study design limits the drawing of causal inferences.…”
mentioning
confidence: 99%
“…33,34 Alcohol consumption was not the significant risk factor of HTN among teachers probably due to the fact that there were very few alcoholics (4.3%) among male teachers only. Study finding showed that 48.6% teachers were physically inactive ( Table 2).…”
mentioning
confidence: 99%
“…8 Furthermore, a meta-analysis of studies between 1995 and 2010 found the pooled prevalence of hypertension to be 13.7%, with an increasing trend and higher rate in urban versus rural areas (22.2% vs 14.3%, respectively). 5 An epidemiological shift has been observed in the prevalence of hypertension in developing countries as compared to developed countries. Studies from India and Bangladesh have shown an upward trend in the prevalence of hypertension.…”
mentioning
confidence: 99%
“…Despite effective therapies and lifestyle interventions, adequate control of hypertension remains a challenge. 5 Modern lifestyle factors are responsible for a growing burden of hypertension: physical inactivity, salt-rich diets with processed and fatty foods and alcohol and tobacco use. High BP can also be secondary to other conditions-kidney disease, for example.…”
mentioning
confidence: 99%